Structural poverty dynamics in urban South Africa: A mixed-methods investigation - Simone Schotte (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper examines the extent and determinants of structural poverty dynamics in South Africa, focusing on the socio economically disadvantaged urban African population. The quantitative analysis using panel data is triangulated with evidence from a qualitative case study integrating focus group discussions and life history interviews conducted in the township of Khayelitsha, Cape Town. Data visuali z ation methods in the form of asset pentagons and livelihood diagrams help illustrate the complex processes, livelihood strategies, and asset dynamics that condition movements int o and out of structural poverty. Results emphasi z e meagre job opportunities for low skilled labour, low schooling quality, and relationships of dependency as important dimensions. Lack of access to financial capital as well as the costs and risks associate d with the geographic location of the urban poor, often residing in precarious areas that are spatially separated from the urban centres, further constrain opportunities.
Keywords: D31; I32; C23; J62; 330; poverty; social mobility; livelihood assets; mixed methods; sub-Saharan Africa; South Africa